Current Concepts in Zika Research - Rodriguez-Morales, Alfonso J. (IntechOpen, 2021)
Zika is an arboviral disease that has caused a significant impact, especially in the Americas after the epidemics in 2015 and 2016. The World Health Organization (WHO) declared it as a Public Health Emergency of International Concern (PHEIC) in 2016, linking it with the Guillain-Barré syndrome and especially the microcephaly and the Congenital Zika Syndrome. The multiple consequences, especially in the central and peripheral nervous system in the short and long term, are still to be better defined. Therefore research on Zika is crucial. This book presents an update of the significant epidemiological and clinical research of Zika over the last years in many aspects and from a multinational perspective.